2020
DOI: 10.1371/journal.pone.0238023
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care in Mozambique: Physicians’ knowledge, attitudes and practices

Abstract: Background Palliative care is an essential part of medical practice but it remains limited, inaccessible, or even absent in low and middle income countries. Objectives To evaluate the general knowledge, attitudes, and practices of Mozambican physicians on palliative care. Methods A cross-sectional observational study was conducted between August 2018 and January 2019 in the 3 main hospitals of Mozambique, in addition to the only hospital with a standalone palliative care service. Data was collected from a self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…Each of the reviewed papers focused on different population groups: doctors, nurses, and mothers, 12 medical students, 13,14 junior and senior doctors, 15 and senior clinicians 16 . Other sets of population include private medical practitioners, 17 physicians, 18 psychiatrists, 19 aged adults 20 and adults 21 . Some papers include other population groups containing the Xhosa ethnic group of South Africa, 22 lay people and health professionals, 23 all patients had life support, 24 oncologists, and registered nurses 25 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the reviewed papers focused on different population groups: doctors, nurses, and mothers, 12 medical students, 13,14 junior and senior doctors, 15 and senior clinicians 16 . Other sets of population include private medical practitioners, 17 physicians, 18 psychiatrists, 19 aged adults 20 and adults 21 . Some papers include other population groups containing the Xhosa ethnic group of South Africa, 22 lay people and health professionals, 23 all patients had life support, 24 oncologists, and registered nurses 25 .…”
Section: Resultsmentioning
confidence: 99%
“…The review noted that some medical professionals would rather inform the patient's family members of the prognosis. This will allow the patient's family to comfort him or her before the disclosure of any medical information 18 . Then the patient would be left with the option of deciding on the preferred treatment or course of action.…”
Section: Resultsmentioning
confidence: 99%
“…Respondents specified that they prefer to utilize PC to continue care when no other therapy options remain, yet many also agree that early referral is beneficial for patients. Previous surveys have shown that oncology providers largely agree that cancer patients should receive PC early in the disease course, but actual referral practices often fall short of this goal [ 14 , 23 ]. This discrepancy may be due to the limited availability of PC services and decisions to reserve PC resources for patients at advanced stages of disease who may be most in need.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Palliative care is one of the care types in the clinical setting. [ 3 ] It is a basic human right for all patients, especially those requiring constant care due to chronic, progressive and excruciating pains caused by chronic malignant and non-malignant diseases. [ 4 ] Palliative care is comprehensive and holistic care provided to patients by an interdisciplinary team of physicians, health-care providers, nurses, psychologists and social workers during hospitalisation and even after discharge.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Palliative care is one of the care types in the clinical setting. [3] It is a basic human right for all patients, especially those requiring constant care due to chronic, progressive and excruciating pains caused by chronic malignant and…”
mentioning
confidence: 99%